Keanekaragaman Serangga Air Di Aliran Sungai Pondo Lembah Palu The Diversity of Water Insects in Pondo River, Palu - Mohammad Kafrianto; Hasriyanty Hasriyanty; Flora Pasaru (Universitas Tadulako, 2018)
ABSTRACT Pondo river discharge its water into Palu bay. The large number of community activities along the river bank can affect its water insect diversity. This study aimed to determine the diversity of the insects in the river water. The insects were surveyed on various locations and samplings were purposively determined based on river condition and community activities along the river. The insects were trapped by a surber net and identified at the laboratory of pest and diseases of Agriculture Faculty. There are 17 species from 13 families and 6 orders found. The six orders are Hemiptera, Coleoptera, Ephemeroptera, Trichoptera, Odonata and Diptera. The dominant species is Acentrella sp from the Ephemeroptera family. The highest species diversity shown by shanon Wiener index was at station one with an index 2.13 whiles the lowest diversity in the river delta with index 0.90. Keywords : Diversity, insects, river.